Pengaruh Cangkang Kerang Laut Terhadap Kuat Tekan Beton - Rahmawati, Neti; Lakawa, Irwan; Sulaiman, Sulaiman (Sultra Civil Engineering Journal (SCiEJ), 2021)
Concrete is one of the most widely used building materials today in terms of physical construction. Concrete is made from a mixture of fine, coarse aggregate, cement, and water with a certain ratio, as well as materials that are usually added to the concrete mixture during or during mixing, to changing the properties of concrete to make it more suitable in certain jobs and more economical, can also be added with certain other mixed materials as needed if deemed necessary. Seashells can be used to mix concrete. This study aims to determine whether the addition of shells aggregate shells in a concrete mixture can affect the mechanical properties of concrete. The specimens used are in the form of cubes with a size of 15cm x 15 cm x 15 cm, consisting of additional concrete coarse and fine aggregate with shell substitution percentage of 0%, 15%, 20% with a total sample of 45, with the planned concrete quality of K225. The use of sea shells in increasing the compressive strength of concrete is better used as fine aggregate than coarse aggregate. The use of sea shells as a substitute for fine aggregates achieves maximum results at 20% composition.